It Is Necessary to Re-understand the Low-Voltage Area in Atrial Fibrillation Patients - Liu, Wei; Li, Shijie; Han, Bing (Frontiers in Cardiovascular Medicine, 2022)
The presence of a low-voltage areas (LVAs) is a major feature of the progression of atrial fibrillation. Typically, the LVA is determined by invasive left atrial voltage mapping. In addition to pulmonary vein electrical isolation, Voltage-guided substrate modification by targeting LVAs in addition to PVI has been shown to be superior to conventional PVI “only” approaches regarding freedom from AF recurrences after ablation. Recent studies have found that some factors can predict the LVZ, which can be used to assess the patient's condition and select an appropriate treatment strategy.